2014
DOI: 10.12968/bjon.2014.23.6.316
|View full text |Cite
|
Sign up to set email alerts
|

Depression among nursing students in an Indian government college

Abstract: It is imperative that the psychological condition of nursing students be viewed as an important aspect to be considered, particularly within the Indian population and others in which there is a paucity of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
1
19
0
8
Order By: Relevance
“…Similar study from West Bengal by Chatterjee et al (2014) (10) found 63.9% prevalence of depression among nursing students.…”
Section: Discussionsupporting
confidence: 63%
“…Similar study from West Bengal by Chatterjee et al (2014) (10) found 63.9% prevalence of depression among nursing students.…”
Section: Discussionsupporting
confidence: 63%
“…Pastaraisiais metais teigiama, kad Amerikoje vienas iš trijų studentų [16], Indijoje 63,9 proc. studentų patiria depresijos simptomus [17].…”
Section: įVadasunclassified
“…studentų nustatyti depresijos simptomai [15], Indijoje depresijos simptomai nustatyti net 63,9 proc. tyrime dalyvavusių studentų [17]. Tuo tarpu estų tyrėjai skelbia, kad iš 413 medicinos studentų 30,6 proc.…”
unclassified
“…Pesquisas tem revelado a importante função protetora do suporte social na vida acadêmica do estudante de enfermagem (Brandy et al, 2015;Ratanasiripong, 2012;Yıldırım et al, 2016), que envolve o apoio da família e amigos (Xu et al, 2014;Chatterjee et al, 2014).…”
Section: Percepção De Suporte Social Entre Estudantes De Enfermagemunclassified
“…Pesquisa na China destaca que o maior apoio social e o bom relacionamento com a família foram associados ao menor nível de estresse e sintomas depressivos (Xu et al, 2014). Na índia, pesquisa revela que a desarmonia familiar, o desinteresse pelo curso e a insegurança sobre o futuro foram fatores de risco para desenvolvimento da depressão entre estudantes de enfermagem (Chatterjee et al, 2014). Estudo envolvendo 1130 estudantes de enfermagem de Coimbra, Portugal, identificou que o maior apoio social está relacionado ao contato mais próximo e frequente com familiares (Leal, Santos, 2016).…”
Section: Percepção De Suporte Social Entre Estudantes De Enfermagemunclassified